Optimising undergraduate medico-legal and professionalism teaching through a student-selected component. Issue 3 (4th August 2021) - Pandya, Tej; Muneeb, Ferhan; Gibb, Jonathan; Metcalfe, Neil H
Abstract : Purpose: We sought to understand how best to teach medico-ethics, law and professionalism to undergraduate medical students using a student selected component. Materials and methods: Students received small-group, seminar-based teaching from the module organiser and external representatives from organisations such as the General Medical Council and Medical Protection Society. Experiential learning was also facilitated through attendance at fitness to practice tribunals and Coroner's court, followed by structured debrief sessions. Two cohorts of medical students(n=40) from Manchester University were surveyed before and after undergoing the placement, with qualitative interviews and thematic analysis for a subset of this group(n=16) and course leaders(n=4). Results: There were significant (p<0.05) improvements in students' self-reported understanding of key medicolegal organisations and accessing guidance on professionalism. Thematic analysis uncovered increasing confidence in the role of the medicolegal system, barriers to challenging unprofessional behaviour, and a desire for this to be placed in the curricula. Conclusions: This placement was well received and demonstrates an importance for this content to be taught effectively in the medical curricula. Having protected time to attend sessions while an undergraduate may reduce anxiety felt by doctors fearing medicolegal proceedings and help challenge unprofessional behaviours. Further work could explore mechanisms into how best to incorporate this into the medical curricula.